Analisis Manajemen Pendidikan Inklusi di SD Negeri Poris Gaga 2 Kota Tangerang - Nurfadhillah, Septy; Ningsih, Dwi Aulia; Haq, Ahmad Syaiful; Andriyanto, Andriyanto; Ramdhan, Fadlatul (Lembaga Yasin AlSys, 2022)
This study aims to determine the learning media of inclusive education programs for children with special needs at SD Negeri Porisgaga 2 Tangerang City, to find out the factors that influence the importance of learning media for inclusive education programs for children with special needs. . Data collection techniques are through observation, interviews and documentation. Sampling is purposive sampling. The validity of the research data is by using data triangulation techniques (source triangulation) and reviewing informants. The data analysis technique used is interactive analysis technique. From the research results, it is known that the implementation of inclusive education programs for children with special needs at SD Negeri Porisgaga 2 Tangerang City goes through 3 (three) stages, namely the preparation stage which includes data collection activities for children with special needs, program socialization and provision of resources. The program implementation phase includes learning implementation activities, capacity building for human resources, and mentoring services for children with special needs, the last stage is the monitoring and evaluation stage.